Smart diagnostics V : selected, peer reviewed papers from the 5th International Congress of Technical Diagnostics, September 3-5, 2012, Krakow, Poland - Uhl, Tadeusz (Key engineering materials ;, 2014)
The aim of the special collection was to bring together the expertise of scientist and engineers from universities and industry in the field of Structural Health Monitoring, Non-Destructive Evaluation, and Condition Monitoring. The study of damage detection, localization and assessment are important in the rapidly growing field of SHM. Due to interdisciplinary character of SHM systems, the contributions come from experts from area of mechanics, materials engineering, electronics, software engineering, and signal processing as well as system users from civil engineering, aviation, power plants,